Carnegie visits nobel: Do inheritances affect labor and capital income? - Mikael Elinder; Oscar Erixson; Henry Ohlsson (Research Institute of Industrial Economics (IFN), 2011)
The objective of this paper is to study when and how much labor supply and savings of heirs respond to inheritances. We estimate fixed effects models following direct heirs, inheriting in 2004, during the years 2000-2008 using Swedish panel data. Our first main result is that the more the heir inherits, the lower her labor income becomes. This labor supply effect appears in the years after the heir had inherited. We also find evidence of anticipation effects that occur before the actual transfer. Our second main result is that the more the heir inherits, the higher her capital income becomes. This savings effect only appears in the years after receiving the inheritance. It disappears after a couple of years.
Keywords: D10; D80; D91; J22; 330; inheritances; bequests; windfall gains; labor supply; capital income; uncertainty; Erbe; Einkommen; Arbeitsangebot; Einkommenshypothese; Schweden